Desain dan Evaluasi Unjuk Kerja Pemanas Induksi sebagai Sumber Panas pada Alat Pirolisis - Suhardi Makmur; Muhammad Daud; Adi Setiawan (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The use of renewable energy for rural electrification in Indonesia has great potential, including the potential for energy from biomass. One way to convert biomass into renewable energy is through the pyrolysis process. Heating technology in pyrolysis is currently under development, one of which uses electrical energy with induction heating technology. Therefore, the aim of this research is to design a pyrolysis tool with a suitable induction heater, where this tool is powered by an electrical energy source. The pyrolysis tool is designed to use an induction heater that is varied by using a three-coil and a seven-coil heating element. The pyrolysis tool design was then realised in prototype form with a length of 1500 mm, width of 1000 mm and height of 1400 mm. Prototype testing was carried out using one heater, with each coil variation operated until the pyrolysis reactor reached the design temperature of 500°C within 120 minutes. The test results of the prototype pyrolysis unit using an induction heater with a three-coil heating element showed that the reactor temperature could not reach the desired target, but only reached a temperature of about 305.6°C in 120 minutes, with the electrical energy required for one test being about 5 kWh. Meanwhile, tests using an induction heater with a seven-coil heating element showed that the reactor temperature target of 500°C in 120 minutes could be well achieved. The electrical energy required for a test using a seven-coil heater is approximately 8 kWh.